The Interrelationship Between Social Anxiousness and Psychological Defense Mechanisms; Advances in Computer Science Research; Vol. 51 : Information Technologies in Science, Management, Social Sphere and Medicine (ITSMSSM 2016) - Shelekhov I. L. Igor Lvovich; Grebennikova E. V. Elena Vladimirovna; Marukhina O. V. Olga Vladimirovna; Berestneva E. V. Elena Viktorovna (2016, 2016)
Title screen